The Libras Law and the right to health promotion for the Deaf in the advent of the COVID-19 pandemic in Brazil: a literature review (Research, Society and Development, 2022)
The year 2020 was atypical for everyone in Brazil and in the world, marked by the SARS-CoV-2 pandemic, the virus that causes COVID-19. But the year was also important for the deaf community because the Brazilian Sign Language Federal Law 10.436 of April 2002, which recognized the Brazilian Sign Language as a language in Brazil, completed 20 years of officialization. In view of these events, this paper aimed to conduct a study in the period that elapsed since the approval of the law and to point out the main changes and advances in the health care for the deaf community provided by it, therefore, this paper also proposed to detect barriers there are still present, being faced by deaf people. For this purpose, we conducted a literature review of the last 20 years since the approval of the Brazilian Sign Language Law, analyzing the main literature and digital academic platforms. Accordingly, we identified in the various authors consulted numerous barriers still faced by deaf people in their access to health such as: the lack of advertisement on health promotion and on health prevention in Brazilian Sign Language for the deaf community; health professionals without proper qualification for adequate care in sign language, in the case of bilingual professionals, requiring a translator/interpreter of Brazilian Sign Language in medical appointments; the non-accessibility of information; difficulties in specific vocabularies and legal inapplicability of rights. It was further concluded that such factors were aggravated by the pandemic, the isolation, and the use of face masks as protective equipment.